The Influence of Work Competence on Work Performance and Its Impact on Job Satisfaction at the Cooperatives and SMEs Department of North Sumatra Province - Agustin, Nia; Hafizah; Pitono (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
This research was conducted at the North Sumatra Cooperatives and UKM Service with the aim of analyzing and knowing the effect of job competence toward job performance and its impact on job satisfaction. The population were 165 employees who worked at Department of Cooperatives and UKM North Sumatra in 2020, with 117 respondents using the Slovin formula. Sources of data using primary data and data collection techniques by surveying giving questionnaires to respondents. Data analysis techniques used data quality, classical assumption test, hypothesis testing. Based on the results of the study, it showed that partially job competence has significantly effected on job performance and employees job satisfaction too, performance has significantly effected on job satisfaction, Job satisfaction did not mediate the effect of job competence on employee work performance in the North Sumatra Cooperative and UKM Service. Job competence and employee performance have a strong correlation with employee job satisfaction. It could be said that job satisfaction of employees of the North Sumatra Cooperative and SME Service can be explained by job competence and work performance of 48.3% and the other amount 51.7% can be explained by other variables not examined.